Spatial dynamics of plasmodium knowlesi vectors and molecular characterization of its parasites in Kudat, Sabah, Malaysia / Wong Meng Li - Wong, Meng Li (2018)
Plasmodium knowlesi is the fifth human malaria and poses a new threat to malaria elimination since there is a naturally existing zoonotic reservoir. In Sabah, P. knowlesi cases were reported in great number in 2012 and 2013 with 815 and 996 cases, respectively. Previous extensive studies had incriminated An. balabacensis as the vector for human malaria. However, significant environmental changes in Sabah due to land conversion from forest to plantations may have displaced the primary vector. Hence, the objective of this study was to determine the spatial dynamics of P. knowlesi vectors in Kudat, Sabah, and to to conduct molecular characterization of its parasites. A one year entomological survey in Kudat, Sabah was conducted using bare leg catch (BLC). A total of 2263 mosquitoes were caught consisting of 1884 anophelines (10 species) and 379 culicines in which An. balabacensis was the predominant species (95.1% of the total caught) while other anophelines were in low numbers. Morphologically identified An. balabacensis, An. introlatus, An. latens, An. cracens and An. macarthuri were confirmed their species status by using mtCOI, ITS2 and 18S gene markers. Restriction fragment length polymorphism analysis of ITS2 amplicons using restriction enzyme Msp I generated six RFLP genotype profiles whereby two of the profiles belong to An. cracens. Also analysis with native acrylamide gel indicated that there are variant present within the ITS2 region of An. cracens. Phylogenetic analysis of mtCOI, ITS2 and 18s showed that collected Leucosphyrus Group of mosquitoes clustered accordingly in their specific clade. The peak biting time of An. balabacensis was between 1800- 2000hrs. Highest density of An. balabacensis was observed January in village (KP), August and November in farm (TD), and relatively low in forest (LL). Range of An. balabacensis caught with varied between 2-28 mosquitoes per night. In addition, the iv high survival rate, parity rate (>50%), sporozoite rate (2-12.50%) and vectorial capacity (>3.0) in An. balabacensis was obtained in this study. There were forty five (3%) An. balabacensis were positive for Plasmodium oocysts (18), sporozoites (14) or both (13) by microscopy. Using human and simian malaria species-specific PCR primers, four simian malaria parasites were detected, namely P. knowlesi, P. inui, P. cynomolgi and P. coatneyi. There were mono-infection and mixed infections (up to quadruple infections) detected in An. balabacensis. Thirteen An. balabacensis were positive for P. knowlesi. The SSU rRNA gene of Plasmodium from 10 isolates of An. balabacensis were amplified, cloned and sequenced. Analysis of the SSU rRNA gene sequences confirmed the identity of the simian malaria parasites that were detected by PCR in the mosquitoes. Genetic analysis of the simian malaria parasites in An. balabacensis in Kudat showed high haplotype diversity indicating they were undergoing expansion. PCR of the pooled dried mosquitoes showed that P. cynomolgi was the predominant simian malaria identified in all study sites. Based on the current entomological findings supported by molecular data, An. balabacensis is a highly competent vector and will continue to pose a risk to human malaria transmission. Thus effective malaria control measures need to be devised and carried out in order for Malaysia to move towards malaria elimination.